Implementasi Pembelajaran Berdiferensiasi pada Materi Teks Laporan Hasil Observasi - Wulandari, Gusti Putu Ayu Trisna; Sudiana, I Nyoman; Yasa, I Nyoman; Handayani, Ni Made Yeni (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – The development of a dynamic cultural life marked by advances in science and technology is an inevitable reality. The curriculum is constantly evolving and improving due to various factors, such as the implementation of the Independent Curriculum. However, based on observations in several schools, especially in secondary schools that have implemented the Independent Curriculum, it is known that learning that considers the diversity of students is still rarely applied in the classroom, including in the Indonesian language subject. Teachers still tend to apply uniform learning. In the field, many teachers are still confused about how to implement differentiated learning. This study aims to analyze differentiated learning in the observation report text material at SMA Negeri 1 Kuta.Method – This research uses a qualitative descriptive research design. The sample in this study amounted to 72 respondents. The data instruments used are observations, observations, and interviews with data validity techniques using data credibility tests with reference materials, member checks, and triangulation.Findings – The results of this research state that the application of differentiated learning in the Observation Report Text material for Class X Students of SMA Negeri 1 Kuta has been carried out optimally and adapts to four basic elements such as content, processes, products, and student learning environments are following the expected goals. Research Implications – This research implies that differentiated learning can be used by teachers to further enhance the products, processes, content, and learning environment that are suitable for students' interests and talents. This aims to ensure students understand the material and achieve the learning objectives.